Social media innovation on consumer buying behaviour - SANKAR, Dr. JEGANATHAN GOMATHI; Mr. DEVANAND.K (The journal of contemporary issues in business and government, 2020)
Online media is fundamental to advanced promoting of brands. Organizations use it to arrive at a huge number of potential and current clients. There are some different web-based media like Instagram, Facebook, twitter, LinkedIn, etc., by which consumer buying behavior is decided. A questionnaire was prepared and data was collected from a sample of 100 consumers who live in and around Chennai. The data was analyzed by variables such as Names of the Social media, Advertisement, and Customization. The findings show that Name of the Social media (0.26) and Advertisement (0.184) having positive linearity. Relationship with respect to Product purchase. The Customization (0.491) has a higher number of positive responses with respect to Product Purchase intention.